"From experts to locals hands" healthcare service planning in sub-Saharan Africa: an insight from the integrated community case management of Ghana - Isaac Annobil; Francis Dakyaga; Mavis Lepiinlia Sillim (BMC, 2021)
Abstract Background Although community participation remains an essential component globally in healthcare service planning, evidence of how rural communities participate in the planning of rural-based healthcare programs has less been explored in Sub-Saharan Africa. Objective We explored communities' participation in health care planning in hard-to-reach communities, within the context of Integrated Community Case Management (iCCM), a community-based health program implemented in Ghana. Methods Qualitative data were collected from eleven (11) hard-to-reach communities through Focus Group Discussions (FGDs), Key Informant Interviews (KIIs) as well as district-level studies (Nadowli-Kaleo, and WA East districts of Ghana). The Rifkin's spider-gram, framework, for measuring and evaluating community participation in healthcare planning was adapted for the study. The results The study found that community participation was superficially conducted by the CHOs. A holistic community needs assessment to create awareness, foster a common understanding of health situations, collaboration, acceptance and ownership of the program were indiscernible. Rather, it took the form of an event, expert-led-definition, devoid of coherence to build locals understanding to gain their support as beneficiaries of the program. Consequently, some of the key requirements of the program, such as resource mobilization by rural residents, Community-based monitoring of the program and the act of leadership towards sustainability of the program were not explicitly found in the beneficiaries' communities. Conclusion and recommendation The study concludes that there is a need to expand the concept of community involvement in iCCM to facilitate communities' contribution to their healthcare. Also, a transdisciplinary approach is required for engineering and scaling up community-based health programs, empowering VHCs, CBHVs and CHAs to realize success.